Reducing Losses in the Supply Chain of Tangerines for Export Through Digital Transformation Strategies: The Peruvian Case - Salvador-Caravedo, Andrea; Fuentes-Castro-Moscoso, Daniella Fernanda; Ruiz-Ruiz, Marcos Fernando; Quiroz-Flores, Juan Carlos; Albarracin-Manrique, Marcos Antonio (LACCEI, 2025)
This descriptive, non-experimental research project with a qualitative approach aimed to propose digital transformation strategies to reduce losses in the export supply chain of tangerines. A systematic literature review was conducted, along with the use of tools such as the Ishikawa diagram and expert interviews to identify the critical factors contributing to the problem. The findings revealed a loss rate of approximately 40% to 50%, primarily during the cultivation and harvesting stages. Additionally, through the use of MICMAC and Regnier’s Abacus tools, the most significant root cause identified was poor control of agroclimatic conditions—specifically, temperature and humidity. Using a SIPOC Turtle Diagram and a conceptual model, the study proposed an integrated system of temperature and humidity sensors during the cultivation stage. This solution demonstrated a reduction in tangerine losses by 10% to 15% and an economic benefit of 3 million dollars. The study presents a viable, adaptable, and cost-effective solution that not only reduces losses but also enhances the competitiveness of the tangerine export sector by improving fruit quality through the integration of technology and technical training.